A Pilot Study of the Effect of Zikir on the Performance Psychology Using Heart Rate Variability (HRV) - Mohd Rozali, Senik; Muhammad Nubli, Abdul Wahab (HeartMath® Institute, 2013)
Zikir has been known to have a direct impact on the individual. Zikir is able to help individuals make behavioral changes. Zikir is known to have an impact on the mind, emotions and behavior. An investigation was conducted to identify the extent implemented zikir able to help individuals make changes themselves. Clinical studies carried out by taking 6 respondents among secondary school students who were involved in the disciplinary problems. Zikir intervention enables us to make changes ourselves using the technique of "Heart Rate Variability" (HRV). Students were given technical chanting slowly, loudly, and several techniques of zikir. Conversion EmWave had recorded using a look at how the students were able to make changes themselves. The study found that students who successfully completed the zikir training able to make changes themselves. Students had successfully made a change to the change score "HRV Coherence" of the VLF spectrum of LF and HF spectrum conditions. The study had found that this technique was very effective and able to be used to help students make the change themselves and improve their academic achievements. This technique can be used in schools to improve the effectiveness of prevention of disciplinary problems therefore enabling education programs to be implemented.